Pengembangan Aplikasi Webgis Perutean Menggunakan Teknologi Geographic Information System (GIS) Open Source - Widyantoro, Bimo Aji; Prayogo, Luhur Moekti (Universitas Trunojoyo Madura, 2023)
Information technology has now become an important part of spatial data management for sustainable geopsasial information planning and development. This research aims to develop webgis routing applications using open source GIS technology capable of providing dynamic routing systems, completing effective routing, and displaying route search results. The system is built with Client-Server architecture design consisting of QGIS as GIS software, OSM as open spatial data provider, HTML, CSS, Javascript as basic programming language, Leaflet, Boostrap, and JQuery as mapping library, XAMPP as Server, PostgreSQL/PostGIS as spatial database management system, Dijkstra as route engine library and PHP as REST API for Web Development Backend. The results showed that the routing WebGIS application was able to run well in finding routes based on the Point of Interest (POI) entered and be able to display the results of alternative routes when there were road closures. Based on the results of the study, the conclusion is the use of open source technology is able to produce a dynamic routing, can be modified, easy in maintenance, and many library options for web mapping.